Body Mass Index in Clinic Attenders: Patient Self-Perception versus Actual Measurements. (24th November 2014) - Pooransingh, S.; Ramgulam, K.; Dialsingh, I.
Abstract : Objectives . The objectives of the study were to measure actual BMI in patients attending chronic disease clinics in health centres and to relate this to the patients' own perceptions of their body image and the need to lose weight. Study Design . A cross sectional study. Methods . The actual BMIs in patients who attended chronic disease clinics in 14 health centres were measured. All participants were asked to state where they thought they were on a visual body image scale and were also asked if they thought they needed to lose weight. Results . All participants approached agreed to participate (RR 100%). 70% of patients were found to have a raised BMI. Approximately 73% of patients using the visual scale indicated that an overweight or obese BMI was ideal for them. Conclusions . Patients think they are thinner than they actually are, with obvious implications for health and health seeking behaviour. A whole of society approach is needed to change weight status perceptions and improve exercise and dietary behaviour.